MELODIA RÓŻNIE NAKRĘCONA - Zaczkowski, Piotr (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
National colours and anthem are the elements of both identity and autocreation of the sport stage’s actor. The behaviour of Olympic champions has been a subject to reviews made in the language of theatre and, sometimes, the language of politics. Nowadays, an Olympic champion, the leading actor of the spectacle, is a self-aware director of the epilogue to their own play, and adds a personal touch to the award ceremony’s scenario. Simultaneously, solidarity with the values that perceive the individual rivalry as a confrontation between countries and nations is expected from an Olympic champion. The acting out of the sports game’s ceremony by its players maintains (despite the evolution of the spectacle itself) a conservative nature that corresponds with the spectators’ ideas. Reports and descriptions available in press and Internet sources were used during the reconnaissance, as well as the relations available in sport’s literature, reportage and journalism.